The Spanish Version of the Fear of Kidney Failure Questionnaire: Validity, Reliability, and Characterization of Living Donors With the Highest Fear of Kidney Failure. Issue 2 (February 2021) - Torres, Xavier; Menjivar, Ana; Baillès, Eva; Rangil, Teresa; Delgado, Isabel; Musquera, Mireia; Paredes, David; Martínez, Montserrat; Avinyó, Núria; Vallés, Carmen; Cañas, Laura; Lorenzo, Dolores; et al.
Abstract : Background: Measures of fear of progression or recurrence of illnesses have been criticized for neglecting cross-cultural validity. Therefore, we assessed the psychometric properties of the Spanish version of the Fear of Kidney Failure Questionnaire (FKFQ), to determine whether postdonation fear of kidney failure (FKF) influenced the donors' psychosocial status, and define variables that characterized donors with high FKFQ scores. Methods: We included 492 participants (211 donors) in a multicenter, 11-year, retrospective, cross-sectional study. Donors were classified with a Latent Class Analysis of the FKFQ-item scores and characterized with a multivariable logistic regression analysis. We calculated the risk ratio based on predicted marginal probabilities. Results: The Spanish version of the FKFQ showed acceptable psychometric properties. FKF was uncommon among donors, but we detected a small subgroup (n = 21, 9.9%) with high FKF (mean FKFQ score = 14.5, 3.1 SD). Compared with other donors, these donors reported higher anxiety and depression (38% and 29% of potential anxiety and depressive disorders), worse quality of life, and less satisfaction with the donation. Donors with high FKFQ scores were characterized by higher neuroticism combined with postdonation physical symptoms that interfered with daily activities. Conclusions: The FKFQ was cross-culturally valid, and thus, it may be used to assess the FKF in Spanish-speaking donors. New interventions that promote positive affectivity and evidence-based treatments for worry could be adapted for treating FKF.